Palliative Care in Advanced Cancer Patients: How and When? - Bruera, Eduardo; Yennurajalingam, Sriram (The oncologist (Dayton, Ohio), 2012)
Learning Objectives After completing this course, the reader will be able to: Discuss the impact of early access to palliative care service on symptom control, quality of life, and cost of care. Formulate strategies to improve early palliative care access through education and research. This article is available for continuing medical education credit at CME.TheOncologist.com Cancer patients develop severe physical and psychological symptoms as a result of their disease and treatment. Their families commonly suffer great emotional distress as a result of caregiving. Early palliative care access can improve symptom control and quality of life and reduce the cost of care. Preliminary results show that early palliative care access can also extend survival. Unfortunately, only a minority of cancer centers in the U.S. have the two most important resources for palliative care delivery: outpatient palliative care centers and inpatient palliative care units. In this article, we use a case presentation to discuss the impact of early palliative care access in light of the currently available evidence, and we recommend ways to improve early access to palliative care through education and research. 摘要 癌症患者常会因为他们自身的疾病或治疗而出现严重的生理和心理症状。患者家属通常也会因为照顾患者而产生很大的情绪困扰。早期姑息治疗可以改善症状控制，提高生活质量以及降低医疗成本。初步结果显示，早期姑息治疗还能够延长患者的生存期。遗憾的是，在美国，仅有少数癌症中心具备提供姑息治疗服务的两个最重要的资源：姑息治疗专科门诊和姑息治疗专科住院科室。在本研究中，我们采用一个案例介绍的方式，根据目前可获得的研究证据，探讨了早期姑息治疗的作用。同时，我们建议通过教育和研究的方式来改善早期进行姑息治疗。 A case presentation is used to discuss the impact of early palliative care access in light of the currently available evidence and ways to improve early access to palliative care through education and research are recommended.